State of Shark and Ray Genomics in an Era of Extinction - Pearce, Jessica; Fraser, Matthew W.; Sequeira, Ana M. M.; Kaur, Parwinder (Frontiers in Marine Science, 2021)
Chondrichthyan species (sharks, rays, skates, and chimeras) are a class of high ecological, economic, and cultural significance, and yet they are the most threatened taxa in the marine environment. The creation of reference chromosome-length genome assemblies allows for conservation genomics methods, such as population and ecological genomics, to be utilized. Despite being greatly threatened and of great importance in maintaining ecosystem function, chondrichthyan species have been repeatedly absent from conservation-based genome sequencing projects. Less than 1% of these species have a genome sequence, despite their almost 50% either threatened or Data Deficient conservation status. Most notably, there are seven orders within this class without any genome representation. In this review, we identify gaps in chondrichthyan genomic resources and demonstrate how the lack of genomic resources for this major taxonomic class is limiting the conservation of these already difficult to conserve species. We highlight other applications for chondrichthyans genomics, such as evolutionary and developmental biology. Likely, the mismatching sampling protocols and limited computational skills and communication between fields have been preventing the integration of marine and molecular sciences. Here, we propose that this field is in dire need to move forward quickly to increase protection for marine species and ecosystems through improved collaboration between marine, molecular, and computer sciences.